Recycled Pd/C-Catalyzed Heck Reaction of 2-Iodoanilines under Ligand-Free Conditions - Zhou, Xiao-Yu; Chen, Xia; Wang, Liang-Guang (Synthesis, 2017)
Recyclable Pd/C-catalyzed Heck reaction of 2-iodoanilines with acrylate has been developed. The reaction occurred readily in 1,4-dioxane using Pd/C (10 wt%) as catalyst under ligand-free conditions, and the cross-coupling products were obtained with medium to high yield. Gram-scale reactions and recycling of the catalyst were also demonstrated.
Keywords: palladium; heterogeneous catalysis; Heck reaction; ligand-free; 2-iodoaniline